فقه الواقع والتنزيل في السياسة الشرعية - الهاشمي, محمد أحمد هلال (Gezira Journal of Educational Sciences and Humanities; مجلد 19 عدد 2 (2022), 2023)
تناولت الدراسة مسألة الاجتهاد التنزيلي الذي يعتمد على فقه الواقع لتنزيل الحكم الشرعي عليه بما يلبي مقاصد الشريعة. تمثلت مشكلة الدراسة في البحث عن منهج ليحكم الاجتهاد الفقهي حتى يكون مواكباً لتطور المجتمعات الإسلامية دون مخالفة للنصوص الشرعية. تكمن أهمية الدراسة في كونها تتناول مسائل النهوض بالفقه الإسلامي حتى يكون متحركاً ومنسجماً مع واقع المسلمين وملبياً لمقاصد الشريعة. هدفت الدراسة إلى بيان المنهج الذي يقوم عليه الاجتهاد الفقهي ليقدم حلولاً للمشكلات التي يواجهها المسلمون جماعات وأفراداً ودولاً، وكذلك رفد الفكر الإسلامي بمنهج تأصيلي للاجتهاد منبثقاً من قواعد الشريعة ومقاصدها. استُخدم المنهج الاستقرائي التحليلي. أهم النتائج أنه لا يجوز النظر إلى الحكم بمعزل عن المقصد الشرعي ثم تطبيقه على الواقع المعين والنظر إلى مآلاته بما لا يؤدي إلى مفسدة في المستقبل. أوصي بمزيد من البحث في هذا المجال لاستكمال مسائل النهوض بالفقه الإسلامي لتجنب الجمود ى البحث الذي ساد حياة المسلمين الخاصة والعامة والانفتاح نحو التجديد انطلاقاً من هذه الأصول والقواعد.   The study dealt with the issue of Al-ijtihad al-tanzili, which relies on the jurisprudence of reality to apply the legal ruling on it to meet the purposes of Sharia. The problem of the study was to search for a method to govern jurisprudence so that it keeps pace with the development of Islamic societies without violating the legal texts. The importance of the study lies in the fact that it deals with issues of promoting Islamic jurisprudence so that it is dynamic and consistent with the reality of Muslims and meets the purposes of Sharia. The study aimed to clarify the approach on which jurisprudence is based to provide solutions to the problems faced by Muslims collectively, individually and states, as well as to provide Islamic thought with a fundamental approach to Al-ijtihad emanating from the rules and purposes of Sharia. The inductive, analytical method was used. The most important results are that it is not permissible to look at the ruling in isolation from the legitimate intention and then apply it to the specific reality and look at its consequences in a way that does not lead to corruption in the future. I recommend further research in this area to complete the issues of the advancement of Islamic jurisprudence in order to avoid the stalemate that prevailed in the private and public lives of Muslims and to open up towards renewal based on these principles and rules.